Meeting Scheduling System: An Approach In Computer Supported Co-Operative Work (CSCW) - Muhammad, Khairul Ronita (2006)
Computer Supported Cooperative Work or commonly well known as CSCW can be referred as a group of people working together in various type of work with assistance from a computer or integrated systems which link with each others. This project specifically focuses on the CSCW application where it discusses on the importance of communications in scheduling meeting.